Adults with complex congenital heart disease have impaired skeletal muscle function and reduced confidence in performing exercise training. (29th August 2020) - Sandberg, Camilla; Thilén, Ulf; Wadell, Karin; Johansson, Bengt
Abstract: Background: Adults with congenital heart disease (ACHD) usually have reduced aerobic exercise capacity compared with controls. However, their skeletal muscle function is less studied. Material and methods: In this cross-sectional study, unilateral isotonic shoulder flexion, unilateral isotonic heel-lift, maximum inspiratory pressure (MIP) and maximum expiratory pressure (MEP) were tested in 85 patients with ACHD (35 women, mean age 36.8 ± 14.8 years), classed as either 'complex' ( n  = 43) or 'simple' ( n  = 42), and 42 age and gender matched controls (16 women, mean age 36.9 ± 14.9). Maximum number of shoulder flexions and heel-lifts were measured. MIP/MEP was tested using a handheld respiratory pressure meter. Exercise self-efficacy, measuring confidence in performing exercise training, was evaluated. Results: Adults with complex lesions performed fewer shoulder flexions compared with controls and patients with simple lesions (28.2 ± 11.1 vs. 63.6 ± 40.4, p  < 0.001 and 28.2 ± 11.1 vs. 54.9 ± 24.9, p  < 0.001), as well as fewer heel-lifts compared with controls and patients with simple lesions (17.6 ± 7.7 vs. 26.3 ± 12.8, p  < 0.001 and 17.6 ± 7.7 vs . 23.2 ± 7.0, p  = 0.024), lower MIP than controls (80.7 ± 26.7 vs. 111.1 ± 29.9 cm H2 O, p  < 0.001) and lower MEP compared with controls (110.8 ± 39.9 vs. 141.8 ± 39.5, p  < 0.001). Their exercise self-efficacy was lower than controls (28.0 ± 8.3 vs. 33.4 ± 6.1, p  = 0.002). In a linear regression model complex heart lesions were independently associated with impaired limb muscle function. Conclusion: Adults with complex congenital heart disease have impaired skeletal muscle function compared with patients with simple lesions and healthy controls. They also had lower confidence in performing exercise training. Thus, this population might have a potential for rehabilitation focusing on improving muscle function and confidence in performing exercise training.